Suppurative Mediastinitis Secondary to Burkholderia Cepacia in a Patient with Cystic Fibrosis - Ronald B George; Yannick Cartier; Alan G Casson; Paul Hernandez (Canadian Respiratory Journal)
Burkholderia cepacia is an important opportunistic pathogen among patients with cystic fibrosis (CF); it is associated with deterioration of lung function, poor outcome following lung transplantation and increased mortality. Fever, an elevated white blood cell count, weight loss and an often fatal deterioration in pulmonary function characterize a particular clinical course, termed ‘Cepacia syndrome’. The present case report describes a 40-year-old man with CF who developed Cepacia syndrome complicated by suppurative mediastinitis, from which B cepacia was isolated. Despite optimal medical and surgical therapy, this patient succumbed to his illness. Those caring for patients with CF should be aware of this potentially catastrophic complication of B cepacia infection, especially in the setting of Cepacia syndrome.